Common drugs causing allergy in patients attending a tertiary care centre in South Kerala - N., Shameem; M. K., Krishna Kumar (International Journal Of Community Medicine And Public Health, 2021)
Background: Drugs play an important part in the wellbeing of human life. Adverse drug reactions are also a part of drug administration. Adverse drug reactions mainly manifest in the form of skin lesions such as urticaria or maculo-papular rash. Drug allergy is a common clinical problem and its assessment is important for appropriate management of the condition. Diagnosis of drug allergy relies on a careful history and in some instance’s allergy testing may be required. Aim was to determine the common drugs causing allergy. Methods: After obtaining informed written consent, data was entered in a schedule and an intradermal test was done in the volar aspect of the patient’s forearm with the selected list of twenty-four drugs. Results: The maximum number of study subjects showed positive reactions were for ampicillin, paracetamol, diclofenac and ketorolac. Conclusions: The drugs which are commonly used by the medical practitioners were found to be more allergic to the study subjects.